(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The e-commerce industry has been greatly impacted by the pandemic, and the number of online businesses has increased, where online shopping has become a trend for consumers. For customers, product information like price, product quality, place/medium, and promotions are very important and should be transparent as they affect their buying choices. Online businesses are competing for customers in a wide market like never before. Customer retention gained increased value in e-commerce. Generally, it is recognized that there is a positive relationship between customer retention and profitability, as customer retention allows a corporation to boost profitability and revenue by constantly purchasing a product from an online store. The findings of the study revealed that the employed and unemployed group of respondents strongly agree that price, product quality, place/medium, and promotions influence customers buying behavior and affect customer retention. Moreover, the results of the study revealed that there is no significant difference between the cited variables. The main problems encountered as to the listed variables were overpricing, product quality being far from the customer’s perceived value, errors in websites, and defective freebies. This study proposed to improve the rate of customer retention by having a strong foundation of marketing strategies, as it can be seen as a big factor that affects the business’s longevity in the industry.